FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN TANGGAP DARURAT PADA AVIATION SECURITY TERHADAP BAHAYA KEBAKARAN DI TERMINAL BANDARA X - Ika Fitriyana; Ekawati Ekawati; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
Fire is an accident which is not desired by everyone and can result in losses. World Fire Statistic Report states that 5-8 million people have had a fire accident. According to Badan Pusat Statistik DKI Jakarta there is increasing number of passengers in X Airport so safeness and secureness of the airport building need to be concerned. The purpose of safeness is preventing damage and losses, including from fire danger, so preparedness for emergency response is needed in attempt of preventing fire accident. This research is purposed to analyze the factors which are related to preparedness for emergency response in Aviation Security to the fire danger in X Airport Terminal. The researcher uses explanatory research with cross sectional approach in this research. There are 54 Aviation Securities used in this research. Based on data analysis using spearman rank test, the dependent variables are knowledge about fire (p-value 0,02); availability of fire safety equipment (p-value 0,019); and fire safety training (p-value 0,02). Meanwhile, the independent variables are age (p-value 0,241); work time (p-value 0,549); and control from occupational safety and health officer (p-value 0,452). The researcher suggests to the company for socializing fire prevention guide and fixing emergency doors, placement of APAR and assembly point.